Surian (Toona sinensis (A. Juss.) M. Roem.) Flowers: Morphology,Phenology, and Insects Visitors - Agus Astho Pramono; Endah R Palupi; Iskandar Zulkarnaen Siregar; Cecep Kusmana (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2016)
Efforts to improve the productivity of a seed source require a deep understanding of reproductive characteristics and environmental factors that affect the seed production. This study aimed to investigate the characteristics of reproduction which include 1) the characteristics of flower morphology and phenology, and 2) the identification of flower visitors of surian. Studies conducted in the smallholder forest in Sumedang, West Java. Surian flowers were compound flower that arranged in panicles shape.When a flower blooms, petals do not open fully, formed like a tube. Male flowers are smaller than female flowers and never bloom, and the male flowers fall first. Branching patterns of surian flower panicle is thyrses, and flowers bloom not simultaneously. The development of flower from buds to bloom takes approximately 12 days, the flowers bloom 1-3 days, development of fruit until ripe takes 5-5.5 months. It is found 12 species of insects visiting flowers, 11 species are considered very small. Insects those are found in large quantities were Thrips and three species of Nitidulidae.